Just make believe - Robinson, Maggie (Robinson, Maggie. Lady Adelaide mysteries, 2020)
"Just another country house party-with a corpse! Poor Lady Adelaide seems to trip over bodies no matter where she goes. This time, it's the home of a friend-the hostess AND murder victim, Lady Pamela Fernald. Looking to solve a murder and possibly stoke the fires of love, Addie knows just who to call-Detective Inspector Devenand Hunter of Scotland Yard. Although Dev and Addie may not be able to rekindle a romance, they must work together to stop another murder. And thanks to Rupert, Addie's late-not to mention, unfaithful-husband, they may have the firepower to do so. Rupert needs to make amends for his louche life on earth, but will relying on an angel to help solve a murder blow up in their faces?"--